Manet y sus teóricos. Ideologías estéticas en los orígenes de la pintura moderna (Itinera, 2019)
It is analysed in these lines how the "aesthetic ideologies" of three fundamental authors, Baudelaire Zola and Mallarmé, intervened in the mythification of Manet as the origin of modern painting. Each one of these ideologies held points of view that the passage of time has assimilated in the notion of "the modern", and all three gather most of the interpretations that this painter has received from the current historiography. A constellation of regulatory ideas is thus composed, with which the notion of modernity is defined.